Molecular communication model through gap junction channel with selective permeabilities - Yang, Yiqun (2013)
With rapid development in biological and nano areas, new communication methods promise novel solutions for various research issues. Due to the simple structure and the limited size of nanomachines, nanonetworks have conspicuous differences from traditional networks. Hence exploratory analysis and theory are expected. Molecular communication, which involves biological components in nanoscale, provides a more compatible approach to medical, environmental and agricultural research. Calcium ion (Ca2+), which is one of the most important universal second messengers in vivo cells, participates actively in the regulation of cellular activities. In this paper, we model the molecular communication system through gap junction channels. We present simulation results for patterned cells with different permeabilities. We analyze the propagation characteristics of intercellular calcium waves which are induced by the diffusion of inositol (l, 4, 5)-trisphosphate (IP3).